Laparoscopic Removal of a Broken Sewing Needle in a Patient with Irritative Bladder Symptoms - Lee, Jun Taik (Korean Continence Society, 2010)
A foreign body near the bladder is rare. Although foreign bodies in the bladder can be easily found and removed by endoscopic transurethral removal, extravesical foreign bodies may require the use of an open or laparoscopic procedure. Here, we report a case of a patient complaining of frequency and urgency in whom an extravesical sewing needle was successfully removed by a laparoscopic approach. A 4.5 cm rusty sewing needle was found between the bladder and the left external iliac vessels and was removed through a 5 mm trocar port by use of endo forceps with no complications.